Store Image and Brand Attitude on Retail Service Quality and Customer-Based Brand Equity among Petrol Stations in Klang Valley, Malaysia - Namsuvayam, A. Murugian (2023)
This thesis examines the relationship between retail service quality and customer-based brand equity. For this reason, it explores the role of store image, chain store image and brand attitude in forming customer-based brand equity of petrol stations in Klang Valley, Malaysia. A pilot study on thirty petrol station customers was used to test the items with Cronbach’s alpha. Self-administered and structured questionnaires were amended accordingly and distributed in front of petrol station in Klang Valley to 450 petrol station customers. The customers were approached personally using purposive and convenience sampling. Screening questions were asked prior to handing over the questionnaire. The completed questionnaires were collected immediately, keyed into SPSS version 25, cleaned and used for initial tests. PLSsc in ADANCO 2.1.1 was used to test twenty hypotheses, addressing six research questions. The outcome indicate physical aspect, reliability and policy dimensions of retail service quality having positive relationships with store image with effect size 0.341, 0.169 and 0.154 respectively. The reliability and policy dimensions show positive relationship with chain store image with effect size of 0.314 and 0.174. The overall RSQ has direct positive relationship with customerbased brand equity but showed weak effect size of 0.056. This indicated the mediating effects of store image and store brand attitude, with bootstrapping quantiles showing no ‘0’ between significance level of 2.5% and 99.5%. Theoretically, even though this study proofs perceived quality is an element of customer-based brand equity, the indirect relationship through store image and store brand attitude pave a stronger path. Furthermore, this study also shows chain store effect on store brand attitude and customer-based brand equity is through store image. Thus, it is important for petrol stations to build individual store image and brand attitude using key retail service quality dimensions.